The level of knowledge about folic acid supplementation among young people - Zych, Barbara; Barnaś, Edyta; Kraśnianin, Elżbieta; Sobolewski, Marek (Polish Journal of Public Health, 2010)
Intoduction. The effectiveness of primary prophylaxis preventing neural tube defects significantly depends on the fact whether information regarding folic acid influence on human organism, passed to the adolescents and young adults within educational programmes, is understood and modifies their attitudes. As numerous causes of civilisation diseases are discussed, an increasing significance is attributed to different environmental factors including a diet deficient in folic acid. Aim. The aim of this work was to present current status of knowledge regarding folic acid supplementation among young people. The practical purpose was to identify deficiencies of knowledge about folic acid supplementation as well as prepare and execute an educational programme in this field. Material and method. The study included 338 students attending high-schools in Rzeszow. An authors’ questionnaire was applied. After verification, the gathered data were subjected to statistical analysis using STATISTICA v.7.2 software. Results. This study showed that the level of teenagers’ knowledge in this field was unsatisfactory. When asked about folic acid source, benefits resulting from its intake, and recommended allowances for this compound, high-school students presented insufficient familiarity with these issues. The fact that girls self-evaluated their knowledge about folic acid supplementation lower than boys (p=0.00001) was surprising.